A multidisciplinary clinic for Filipino patients with skeletal dysplasia: Opportunities and Challenges - Maria Melanie Liberty B Alcausin; Ebner Bon G Maceda; Gracia Cielo E Balce; Joycie Eulah H Abiera; Maria Glorian B Tomen (Global Journal of Rare Diseases - Peertechz Publications, 2020)
Purpose: Skeletal dysplasias comprise a heterogenous group of genetic disorders that have generalized abnormalities in cartilage and bone. Although individually rare, collectively it is common with an estimate of 1 in 2000 to 3000. Individuals with skeletal dysplasias are known to be at risk for a myriad of medical complications associated with their conditions; hence a multidisciplinary approach to care is essential. This paper describes the opportunities and challenges in the creation of a multidisciplinary clinic for Filipino patients with skeletal dysplasia. Materials & methods:  A multidisciplinary clinic for Filipino patients with skeletal dysplasia was started. This is the first of its kind and made possible with the collaboration of the Departments of Pediatrics, Orthopedics and Rehabilitation Medicine of the Philippine General Hospital, in coordination with the Big Dreams for Little People - Philippines, an organization of Philippine-based people with dwarfism.  Results: A total of 25 patients in 21 families were seen in the clinic. 13 of the 25 patients (52%) were diagnosed clinically with achondroplasia. Medical concerns include hearing difficulty (3/25), low back pain (7/25), hip pain (2/25), ankle pain (1/25), and obstructive sleep apnea (1/25). Six of the 25 needed regular physical therapy. Conclusion:  Despite the limitations of molecular confirmation in many skeletal dysplasias and the challenges brought about by the Covid-19 pandemic, the multidisciplinary clinic for Filipino patients with skeletal dysplasia allowed awareness of patients and physicians of this group of disorders. In addition to better care directed towards the medical concerns of this special population, it is also hoped to improve health-seeking behavior of patients as access to healthcare is available.